THE EFFECT OF PUBLIC ACCOUNTANT REGULATIONS AND ETHICS CODE OF PUBLIC ACCOUNTANT PROFESSION TO ACCEPTANCE AN AUDIT ENGAGEMENT (Case study on KAP in East Java ) - Trilaksono, Chrisandi; Ismail, Zulfikar (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study was conducted to determine the effect of Public Accountant Regulations and Ethics Code of Public Accountant Profession to acceptance an audit engagement on KAP in East Java. Data analysis method used is multiple linear regression with the F - test and t - test. The results of this study concluded that the  Public Accountant Regulations  and  Ethics Code of Public Accountant Profession  have a simultaneous effect on  accepatance an audit engagement. The results of the coefficient of determination (R2) indicates that the value of Adjusted R Square is 54,1 %, which means that 54,1 % acceptance of an audit engagement is influenced by the Public Accounting Regulations and Ethics Code of Public Accountant Profession, while the remaining 45,9 % influenced by other factors.  Keywords :  Public Accounting Firm, Public Accountant Regulations, Ethics Code Public Accountant Profession, Acceptance an audit engagement.